198k views
0 votes
Completing the square method: 5x squared+13x-6=0​

User Pidge
by
5.1k points

1 Answer

1 vote
Divide through by 5

5/5 x^2 + 13/5 x - 6/5 = 0/5

Which gives

X^2 + 13/5 x - 6/5 = 0

Move constant to right

X^2 + 13/5 x = 6/5

Take half of x term and square it

(13/5 * 1/2)^2 = 169/100

Add to both sides

X^2 + 13/5 x+ 169/100 = 6/5 +169/100

(X +13/10)^2 = 289/100

Root both sides

X + 13/10 = +- root(289/100)

Simplify

X + 13/10 = +- 17/10

X= -13/10 +- 17/10

Therefore

X = -13/10 +17/10

Or

X = -13/10 - 17/10

Which becomes

X=0.4 and x=-3

Hope this helps
User Paco Abato
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.